Food and women’s bodies in Anglophone feminist critical dystopias: from text to context following the pattern of the “hyper-materialization” (Altre Modernità, 2024)
Food is a theme of crucial importance in contemporary feminist critical dystopias, functioning as a symbol of both household hierarchization and market dynamics of production and consumption. As such, food can be a useful interpretative key to connect dystopian fiction to the state of the world outside the literary text. In order to explore this connection, I will argue that food is exploited by dystopian systems of organization through a process which I term “hyper-materialization”: reducing women to their (re)productive roles through both a metaphorical and a concrete association with food, women’s agency is stifled and their productivity is maximized. Following these premises, many of the potentially positive endings characterizing the genre can be framed as a recovery of food’s immaterial dimensions of desire, pleasure and affection. It will be argued that these can be interpreted as the analytical way out of the dystopian novel, compelling readers to bring such resistant practices into their material and situated contexts. To demonstrate the diachronic permanence of this pattern across geographic divides, my analysis will consider The Handmaid’s Tale by Margaret Atwood (1985) along with two contemporary texts from the United Kingdom: Sweet Fruit, Sour Land (Rebecca Ley, 2018) and The Water Cure (Sophie Mackintosh, 2018).